Raising the bar (22). Issue 4 (2nd October 2022) - Elhorst, Paul; Abreu, Maria; Amaral, Pedro; Bhattacharjee, Arnab; Bond-Smith, Steven; Chasco, Coro; Corrado, Luisa; Ditzen, Jan; Felsenstein, Daniel; Fuerst, Franz; McCann, Philip; Monastiriotis, Vassilis; et al.
ABSTRACT: This editorial summarizes the papers in issue 17(4) (2022). The first paper combines input–output modelling with priority weighting to analyse supply-chain impacts of disasters. The second paper examines skill-based functional specialization of value chains in Brazil using interregional and international value-added measures. The third paper questions the common belief that agglomeration economies are the driving force behind cluster formation using an agent-based model. The fourth paper applies modern instrumental variables techniques to measure the impact of forced migration flows from Venezuela to Colombia on house prices. The fifth paper explores the impact of an ageing population on per capita labour income, consumption and wealth at the regional level using a multivariate spatial econometric model. The sixth paper examines the impact of neighbouring countries on migrants' aggregate decisions to remit based on an advanced spatial econometric origin–destination model.